Pengaruh Variasi Ukuran Biji Terhadap Perkecambahan Acacia Fauntleroyi (Maiden) Maiden and Blakely - Mangadas Lumban Gaol; J.E.D. Fox (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
The aim of this study was to investigate to what extent are germination of A. fauntleroyi affected by seed size. Does pre-treatment improve germination? Under what temperature regime does most seed germinate? Three seed size classes (small, medium and large) were chosen. Seeds were pre-treatments either at ambient, 50°C, 75°C or 100°C and incubated at 15°C or 30°C. Then, number of seed that germinate and speed of germination were measure. Five seeds representing each of small, medium and large seed sizes were also selected and the seed coat thickness measured. Seed size, pre-treatment temperature and incubation temperature all affected the number of seed that germinated. Pre-treatment temperature affected germination more than incubation temperature. Incubation temperature affected germination more than seed size. The interaction of seed size and pre-treatment temperature was stronger than that between seed size and incubation temperature. Small seeds produce less germination than medium or large seeds, however small seed germinated sooner. Seed coat thickness varied among seed sizes. Thinner seed coats occur in smaller than larger seeds.